THE INFLUENCE OF KNOWLEDGE AND ATTITUDES OF MIDWIVES TOWARDS PROVIDING VITAMIN K IN THE WORKING AREA OF THE PEBAYURAN HEALTH CENTER, PEBAYURAN DISTRICT - Rosmiati, Rina; Sahrudi, Ns. (HEARTY, 2025)
Background: Newborn babies are very vulnerable to vitamin K deficiency. When in the womb, babies do not get enough vitamin K, because it is difficult for vitamin K from the mother to cross the placenta. When a baby experiences bleeding due to a lack of vitamin K or Bleeding due to Vitamin K Deficiency (PDVK), the baby's body will not stop bleeding because the body is unable to clot the blood due to a lack of vitamin K. This bleeding can occur in various parts of the body, internally or externally. outside. Research Objective: To determine the influence of midwives' knowledge and attitudes on the provision of Vitamin K in the Pebayuran Community Health Center working area, Pebayuran District. Research Method: This research is descriptive analytical with a cross sectional approach. The population in this study were all 37 registered midwives in the Pebayuran Community Health Center Working Area. To determine the sample using total sampling. Research Results: The results show that the significance level is ˂0.001, which means it is lower than 0.05, so the hypothesis is accepted, namely that there is an influence of midwife knowledge and midwife attitudes towards giving vitamin K in the Pebayuran Community Health Center working area, Pebayuran District. With an OR value of 16.4, which means that a midwife who has good knowledge has a 16.4-fold potential for providing Vitamin K and an OR value of 23.9, which means a midwife who has a positive attitude has a 23.9-fold potential for providing Vitamin K. Conclusions and Suggestions: There is an influence of the knowledge and attitudes of midwives on the provision of Vitamin K in the Pebayuran Community Health Center Work Area, Pebayuran District. For the community health center, it can be used as information and evaluation regarding the provision of Vitamin K to newborn babies and for the head of the community health center it is recommended to hold outreach activities regarding the importance of giving Vitamin K to newborn babies and it is mandatory for all health workers to participate so that they understand the dangers of vitamin K deficiency in particular. in newborn babies.